Analisis Karakteristik Antivirus Berdasarkan Aktivitas Malware menggunakan Analisis Dinamis - Ma'arij Haritsah; Adityas Widjajarto; Ahmad Almaarif (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Malware, short for “Malicious Software”, is a program specifically designed to perform an activity that can harm software on a victim's device. Examples of commonly found malware include trojans, ransomware and downloaders. It is important for computer users to recognize and avoid malware when using computer devices. Therefore, computer users can overcome malware attacks by using protection software specifically for computer devices using Antivirus software designed to prevent, find, detect, and remove the types of malware that have been mentioned previously. In this study, the dynamic analysis method is used to determine malware activity by running it and monitoring the activity that occurs. This method is usually used to identify the actions that malware performs when it runs. The results showed that the higher the number of malware activities, the higher the metrics tested on the antivirus, such as CPU, memory, disk, and scan time. Regarding the removable drive protection feature, Avast antivirus is relatively more efficient compared to other antiviruses because it has an average CPU usage, low memory, a fairly high detection rate, and fast scan times. Kaspersky Antivirus is relatively the most effective in detecting malware samples with the highest detection rate of 100%. Meanwhile, the Windows Defender antivirus is relatively the weakest in terms of detection rate because it has the lowest detection rate.